Data Base Manajemen Sistem dalam Inventaris Sarana Prasarana di SMK Pasundan Cijulang - Bela Safitri; Dheca Dheca; Nuryadin Nuryadin (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2023)
The purpose of this study is to analyze the use of database management systems in inventorying infrastructure. This research method uses qualitative methods with data collection techniques of interviews, observation and documentation. The data analysis technique used the Miles and Huberman technique and tested the validity using the triangulation technique. The results of this study, namely based on observation results, it can be seen that 1) the database management system at SMK Pasundan Cijulangis only carried out in managing the inventory of infrastructure facilities 2) the process of inventorying infrastructure facilities, namely in the process of inventorying goods and the process of borrowing goods. 3) The use of inventory databases in the infrastructure process at SMK Pasundan Cijulang was carried out based on Microsoft Excel.